Building the foundations for sustainable development: a case for global investment in the capabilities of adolescents. Issue 10104 (14th October 2017) - Sheehan, Peter; Sweeny, Kim; Rasmussen, Bruce; Wils, Annababette; Friedman, Howard S; Mahon, Jacqueline; Patton, George C; Sawyer, Susan M; Howard, Eric; Symons, John; Stenberg, Karin; Chalasani, Satvika; et al.
Summary: Investment in the capabilities of the world's 1·2 billion adolescents is vital to the UN's Sustainable Development Agenda. We examined investments in countries of low income, lower-middle income, and upper-middle income covering the majority of these adolescents globally to derive estimates of investment returns given existing knowledge. The costs and effects of the interventions were estimated by adapting existing models and by extending methods to create new modelling tools. Benefits were valued in terms of increased gross domestic product and averted social costs. The initial analysis showed high returns for the modelled interventions, with substantial variation between countries and with returns generally higher in low-income countries than in countries of lower-middle and upper-middle income. For interventions targeting physical, mental, and sexual health (including a human papilloma virus programme), an investment of US4·6 per capita each year from 2015 to 2030 had an unweighted mean benefit to cost ratio (BCR) of more than 10·0, whereas, for interventions targeting road traffic injuries, a BCR of 5·9 (95% CI 5·8–6·0) was achieved on investment of 0·6 per capita each year. Interventions to reduce child marriage (3·8 per capita each year) had a mean BCR of 5·7 (95% CI 5·3–6·1), with the effect high in low-income countries. Investment to increase the extent and quality of secondary schooling is vital but will be more expensive than other interventions—investment of 22·6 per capita each year from 2015 to 2030 generated a mean BCR of 11·8 (95% CI 11·6–12·0). Investments in health and education will not only transform the lives of adolescents in resource-poor settings, but will also generate high economic and social returns. These returns were robust to substantial variation in assumptions. Although the knowledge base on the impacts of interventions is limited in many areas, and a major research effort is needed to build a more complete investment framework, these analyses suggest that comprehensive investments in adolescent health and wellbeing should be given high priority in national and international policy.